2012
DOI: 10.1007/s12237-012-9482-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term and Interannual Variability in Primary Production in the Low-Salinity Zone of the San Francisco Estuary

Abstract: We measured primary production during springsummer 2006-2007 to determine the carbon supply to the low-salinity pelagic food web of the San Francisco Estuary (SFE). Weekly or biweekly samples were taken at three stations of fixed salinity for size-fractionated primary production and biomass, both as chlorophyll and from biovolume based on counts. Error variance in productivity estimates arose mainly from the depth integration of 14 C uptake, showing the importance of productivity measurements at high light lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 80 publications
(107 reference statements)
2
53
0
Order By: Relevance
“…50% of surface irradiance) uptake rate was representative for the euphotic zone. The euphotic zone depth (1.05 m) was calculated from a mean Suisun Secchi depth of 0.3 m and the empirical relationship between Secchi depth and light attenuation coefficient as determined for Suisun Bay by Kimmerer et al (2012). The euphotic zone N uptake was scaled to the ratio of the euphotic zone depth to the mean depth of Suisun Bay (5.61 m) and provided in Peterson et al (1985).…”
Section: Model Runs With Variable Flow Fully Mixed Water Column Witmentioning
confidence: 99%
See 2 more Smart Citations
“…50% of surface irradiance) uptake rate was representative for the euphotic zone. The euphotic zone depth (1.05 m) was calculated from a mean Suisun Secchi depth of 0.3 m and the empirical relationship between Secchi depth and light attenuation coefficient as determined for Suisun Bay by Kimmerer et al (2012). The euphotic zone N uptake was scaled to the ratio of the euphotic zone depth to the mean depth of Suisun Bay (5.61 m) and provided in Peterson et al (1985).…”
Section: Model Runs With Variable Flow Fully Mixed Water Column Witmentioning
confidence: 99%
“…Studies have concluded that most levels of the food web above the primary producers are food limited (Müller-Solger et al, 2002;Kimmerer et al, 2005;Sobczak et al, 2005;Greene et al, 2011). The estuary has chronically low primary production (Kimmerer et al, 2012) near the bottom of estuaries listed in order of annual primary production (Boynton et al, 1982;Nixon, 1988). Suisun Bay in the northern SFE (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the studies are usually restricted to monthly, bimonthly or even seasonal sampling campaigns, and few have employed approaches focusing on the variability at smaller time scales. More refined investigations have revealed a greater complexity in the temporal variation in primary productivity, composition and biomass of phytoplankton in estuaries (Fujita and Odebrecht 2007, Cloern and Jassby 2010, Kimmerer et al 2012) than was evident in early studies. Small-scale variability may be related to weather events, such as fronts and episodes of heavy rainfall, as well as variations in the tidal level, local currents, concentration of dissolved nutrients and the rates of grazing and competition.…”
Section: Introductionmentioning
confidence: 99%
“…Located at the interface between the continental and oceanic environments, estuaries are influenced by both and are dynamic ecosystems with high complexity and marked variability in their physicochemical characteristics, which directly affect the rates of primary productivity and the composition and abundance of phytoplankton. This variability is determined by seasonal cycles of solar irradiance, rainfall, winds and tides, which act together in different temporal and spatial scales (Jouenne et al 2005, Abreu et al 2010, Kimmerer et al 2012). …”
Section: Introductionmentioning
confidence: 99%